Nitrogen and Sulphur Relations in Effecting Yield and Quality of Cereals and Oilseed Crops - B.K. Nad; T.J. Purakayastha; D.V. Singh (The Scientific World Journal)
Nitrogen and sulphur, both vital structural elements, are especially needed for the synthesis of proteins and oils. Investigations revealed the required application of sulphur is one half to one third the amount of nitrogen, and the ratio becomes narrower in mustard (Brassica juncea L.), followed by wheat and rice. The efficiency of an increased level of nitrogen required a proportionately higher amount of sulphur. A critical investigation on the effective utilization of applied vis-à-vis absorbed nitrogen in wheat and mustard envisaged accumulation of NO3-N in vegetative parts when sulphur remained proportionately low. Application of sulphur hastened the chemical reduction of absorbed NO3– for its effective utilization. The effect was more pronounced in mustard than in wheat. Easily available forms of sulphur, like ammonium sulphate and gypsum, as compared to pyrite or elemental sulphur, maintained adequate N to S ratio in rice, resulting in a reduction in the percent of unfilled grain, a major consideration in rice yield. A narrow N to S ratio, with both at higher levels, increased the oil content but raised the saponification value of the oil, a measure of free fatty acids. Whereas, a proportionately narrow N to S ratio at moderate dose resulted in adequately higher seed and oil yield with relatively low saponification value, associated with increased iodine value of the oil, indicating respectively low free fatty acids and higher proportion of unsaturated fatty acids, an index for better quality of the oil.